Differential impact of abnormal vaginal colonization on perinatal outcome and association with early-onset neonatal sepsis: preterm labor vs. preterm premature rupture of membrane. (12th December 2022) - Kwon, Do Youn; Seo, Mi Rang; Park, Hyea; Kim, Seo-Yeon; Sung, Ji-Hee; Choi, Suk-Joo; Oh, Soo-young; Roh, Cheong-Rae
Abstract: Objective: The purpose of this study was to check whether the impact of abnormal vaginal colonization on perinatal outcomes would be different in patients with preterm labor (PTL) and premature membrane rupture (PPROM). We also sought to determine the concordance rate of microorganisms isolated from the maternal vagina and neonatal blood in cases of early-onset neonatal sepsis (EONS) in PTL and PPROM. Methods: This retrospective study included 996 singleton pregnancies who were admitted to the high risk care unit of our institution due to PTL ( n  = 519) or PPROM ( n  = 477) and underwent vaginal culture examination at admission between January 2005 and April 2019. Abnormal vaginal colonization was defined upon isolation of aerobic microorganisms. The maternal baseline characteristics, delivery, and neonatal outcomes were compared according to the presence or absence of abnormal vaginal flora, both in PTL and PPROM. Results: The rate of abnormal vaginal colonization in PTL and PPROM was 17.0 and 21.4%, respectively. Both in PTL and PPROM, the gestational age at admission was lower in the abnormal vaginal colonization group (PTL, 27.2 ± 3.5 vs. 28.2 ± 3.5 weeks, p = .024; PPROM, 26.1 ± 5.3 vs. 27.5 ± 4.5 weeks, p = .007). Multivariable analysis demonstrated that the group with abnormal bacteria in PPROM but not in PTL had a significantly higher rate of EONS than the group without abnormal bacteria after adjustment for confounders including gestational age at admission (PPROM, odds ratio, OR [95% confidence interval, CI]: 4.172 [1.426–12.206]; PTL, OR [95% CI]: 0.661 [0.079–5.505]). Concordance analysis showed that the maternal vaginal bacteria colonization by Escherichia coli (5.9 vs. 0.5%, p = .033) and Staphylococcus aureus (14.3 vs. 0.2%, p = .032) in PPROM was significantly correlated with the microorganisms from the neonatal blood culture EONS cases. In PTL, no specific microorganisms showed concordance between maternal vaginal bacteria and microorganisms causing EONS. Conclusion: Our data showed that maternal vaginal colonization in PPROM, but not in PTL, is an independent risk factor for EONS.